A Review on Water Footprint Assessment and Water-Food-Energy Nexus for Electronic and Food Products - Bong, P.X.H.; Malek, M.A.; Noor, Z.Z. (International Journal of Engineering and Technology, 2018)
Water Footprint Assessment (WFA) has emerged as a new interdisciplinary field of study, that specialize in the study of water use, scarcity, and pollution, in respect to production, consumption, and trade of water-intensive products and services. It consists of the analysis of various techniques and practices, policy plans, and governance mechanisms that contributed to the rise of sustainability, efficiency, and equitability of water footprints. This study focuses on WFA specifically for electronic and food manufacturing products. It determined contributions of different players namely the governments, companies, investors and civil society. This study typically reviews water use in relation to demand for electronic products, food and energy used. It appraisals the sustainable water use translated into coherent food, energy, incentives and trade policies. Water-Food-Energy (WFE) nexus from the perspective of electronic and food manufacturing products are also reviewed. In this study, the challenges in estimating water footprints and WFE nexus for electronics and food manufacturing products include the understanding of various levels of demand, geographical, temporal variations, assessment of uncertainties involved, and the assessment of water-footprint related problems and solutions. The outcomes showed that combining several methods of WFA can obtain adequate results for the water footprint accounting. The WFE nexus is preferred to use life-cycle assessment (LCA) method to identify the environmental impacts. The significances of this study are to raise the awareness on water usage in the supply chain process of the electronic and food products then recommend good practices in water usage.